1998
DOI: 10.1002/(sici)1097-0142(19980801)83:3<498::aid-cncr19>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the breast in males

Abstract: BACKGROUND Breast carcinoma in males is infrequent, and information regarding the results of modern treatment is limited. Cases of breast carcinoma in males were accrued from multiple hospitals in one region to determine treatment, survival, and prognostic factors. METHODS A retrospective review was performed of 217 cases of breast carcinoma in males accessioned at tumor registries of 18 health care institutions in eastern Wisconsin between 1953 and 1995. RESULTS Of the 217 cases, 215 (99.1%) were carcinomas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(44 citation statements)
references
References 25 publications
1
38
1
1
Order By: Relevance
“…The prevalence of comorbidities increased with age, which likely contributed to the decreased OS in MBC than FBC. Donegan et al [16] reported that the high rate of post-treatment mortality from comorbidities, such as heart disease or other cancer types, was a major contributor to the poor survival observed in MBC. In our population-based comparison, MBC had more advanced stages (stages II-IV), lower grades, larger sizes, more lymph node and distant metastases than FBC.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of comorbidities increased with age, which likely contributed to the decreased OS in MBC than FBC. Donegan et al [16] reported that the high rate of post-treatment mortality from comorbidities, such as heart disease or other cancer types, was a major contributor to the poor survival observed in MBC. In our population-based comparison, MBC had more advanced stages (stages II-IV), lower grades, larger sizes, more lymph node and distant metastases than FBC.…”
Section: Discussionmentioning
confidence: 99%
“…Older age at diagnosis is associated with a higher prevalence of comorbidities, which likely explains the overall poorer survival among male compared with female breast cancer patients. Donegan et al [8] reported that a major contributor to the poor survival in male breast cancer patients was from the high rate of post-treatment mortality from comorbid disease. Approximately one third of post-treatment deaths were due to heart disease or other non-breast cancers [8].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the risk factors implicated include diet (10), alcohol intake, obesity (11), tobacco abuse, and conditions associated with increased estrogen or decreased androgen, medications, or radiation exposure (12). Similar to the case of breast carcinoma in females, a family history of breast cancer in men or women MBC patients had fewer months of survival than did control patients.…”
Section: Discussionmentioning
confidence: 99%